Harmonization of the code of ethics of the Indonesian National Police and restorative justice principles in the settlement of traffic accident cases - Kurniawan, Dicki Agri; Sara, Rineke (International Journal Labs, 2024)
Traffic accidents are unintended events on the road involving at least three vehicles, with or without other road users, and can result in casualties and material losses. The Indonesian National Police serves as a law enforcement apparatus that is at the forefront of creating order and justice in the lives of society, nation, and state. The harmonization between the Police Code of Ethics and the principles of restorative justice in resolving traffic accident cases is crucial for creating a more comprehensive and sustainable justice system, as well as meeting the public's expectations for a better legal system. This research will review various regulations governing traffic accidents, the Traffic and Road Transport Law (UU LLAJ), and the police code of ethics, and analyze the implications of these regulations on law enforcement practices in the field. The results of this research indicate that there is a pressing need to align both aspects in order to facilitate more effective and equitable law enforcement. With the right steps, it is anticipated that law enforcement in traffic accidents in Indonesia can become more just, transparent, and effective, thereby enhancing the overall quality of justice in society.